Medical Problems in a sample Of Iraqi dental patients (Mustansiria Dental Journal, 2018)
Medical status of 679 subjects, who attended a dental department in one of thepublic clinics in Baghdad, was examined, significant medical histories were found in133 (19.5%) of the subjects. They included diabetes mellitus (5.31%), hypertension(3.54%), and peptic ulcer (2.21%), adverse drug reactions (1.18%), neurologicaldisease and (0.88%), and blood disorders (0.20%).